Increased circulating chemerin in patients with advanced carotid stenosis - Adrian Kammerer; Holger Staab; Maria Herberg; Christine Kerner; Nora Klöting; Gabriela Aust (BMC Cardiovascular Disorders, 2018)
Abstract Background Chemerin is an adipokine which plays a crucial role in atherosclerosis. Here, we examined whether circulating chemerin is enhanced in patients with advanced carotid stenosis. Methods Chemerin was quantified in 178 patients prior to carotid end arterectomy (CEA) and in age- and gender-matched controls (n = 163). Chemerin levels were related to anthropometric, clinical and metabolic characteristics of the patients. Results Chemerin levels were higher in patients compared to controls (p <  0.001). Chemerin correlated to parameters associated with inflammation such as C-reactive protein (CRP, p <  0.001), leukocyte blood count (p <  0.001) and circulating TNF-α (p = 0.004) in the patients. Chemerin levels did not differ between asymptomatic (n = 93) and symptomatic patients who experienced an ischemic event within 6 months prior to CEA (n = 85). However, in the case of high-grade carotid stenosis (≥ 90%), chemerin levels were higher in symptomatic (n = 44) compared to asymptomatic patients (n = 41, p = 0.014). Chemerin was increased in patients with (n = 50) compared to patients without (n = 128) coronary artery disease (CAD, p = 0.002). A high level of chemerin increases the risk for CAD in patients (p = 0.0013). Conclusions Circulating chemerin is increased and correlates to inflammatory parameters in patients with advanced carotid stenosis.